Pengaruh Senam Nifas Terhadap Involusi Uteri Pada Ibu Nifas Di rumah Sakit Khusus Daerah Ibu Dan Anak Siti Fatimah Makassar - Rosmina Situngkir (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2019)
This study aimed to determine the effect of postnatal gymnastics on the speed of uterine involution on post partum mother in RSKDIA Siti Fatimah Makassar. The type of research was a Pre Experimental Design. The number of samples were 30 respondents group of normal post partum mothers who were divided into 2 groups: 15 respondents were treated with puerperal exercises and 15 respondents were not given postnatal gymnastic treatment. The sample was chosen by non probability sampling using purposive sampling technique. The samples were observed on the 7th day after postnatal exercises in the case group and in the control group were observed to see the difference in uterine involution rate. The statistic test was a Mann-Whitney Difference test with significance ? = 0,05 got p value = 0,001, it showed that p value <0,05 and can be concluded alternative hypothesis (Ha) accepted and null hypothesis (Ho) Rejected means there was the influence of puerperal gymnastics on the speed of involution of uteri on postpartum mother at RSKDIA Siti Fatimah Makassar. This study revelead that many postpartum mothers experience a rapidly changing speed of uterine involution in categorical terms. Therefore, for health workers it is suggested to developed a good motivation to post partum mother to do gymnastic gymnastic either through counseling or through leaflet and poster.